Mohammad Ali Pasha, a pioneer of modernization and renewal in Egypt and his perception of modernity - ولی ا... برزگر کلیشمی; زهرا خدایی قشلاق (پژوهش‌های تاریخی ایران و اسلام, 2014)
The presence of classic colonialism in Muslim countries bought a common feeling of helplessness and serious backwardness in Muslim communities. It caused a continuous intellectual challenges in different fields between intellectual and political elites of the Islamic societies, to find a solution and remedy for that. In Egypt, for the first time this mental controversy due to comparison between Egypt’s inferiority and West’s superiority came in light and was expressed by Muhammad Ali Pasha. By reviewing his reformative measures it can be understood that according to his view point, the origins of European power were rooted in their success and hold on modern science and technology. Therefore, the formation of reformative policies of Muhammad Ali Pasha was based on western model and pursuing their policies. His stance towards modernity and western progression was lacking integration and had a contradictory nature. He has praised from one hand the new sciences and technology of the West and on the other, has not accepted all the necessities and requirements of modernity and sometimes his policies were in contradiction with the nature and spirit of modernity. In this article, we will analyze the reformative policies and measures of Muhammad Ali Pasha and the stances of the pros and cons of his policies and its consequence of reform carried on Egyptian society, it will attempt to elucidate the role of Mohammad Ali Pasha in order to advance the process of renovation and modernization in Egypt, and seen a picture of his understanding of modernity is also provided.